Korelasi Mengajar Variatif Guru Pendidikan Agama Kristen terhadap Prestasi Belajar Siswa SMP BOPKRI Wonosari, Yogyakarta - Yermi Ndun, Yufri (Student Evangelical Journal Aiming At Theological Interpretation, 2024)
One of the factors that influences student achievement is the teacher's way of teaching. Teaching methods are part of pedagogical competence which includes the quality of teacher learning which determines student understanding. Teachers who are varied in teaching are also teachers who have the openness to want to learn about the facilities and infrastructure that exist in a school institution to support the ongoing learning process. This research uses a descriptive method approach with the aim of obtaining certainty about the results of the relationship between teacher teaching methods and student learning achievement (N= 46 respondents). The results of the research show that the t test result (r count) is 0.628, which if the r table is 0.291, then the t test result > t table (0.628 > 0.291) for the number of respondents (N= 46). Based on the correlation coefficient in the criteria above, it can be stated that there is a relationship between the Variative Teaching Correlation variable for Christian Religious Education Teachers (X) and Student Learning Achievement (Y) at BOPKRI Wonosari Middle School of 0.628, which is classified as high correlation.